Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-short.115
|View full text |Cite
|
Sign up to set email alerts
|

BERTTune: Fine-Tuning Neural Machine Translation with BERTScore

Abstract: Neural machine translation models are often biased toward the limited translation references seen during training. To amend this form of overfitting, in this paper we propose fine-tuning the models with a novel training objective based on the recently-proposed BERTScore evaluation metric. BERTScore is a scoring function based on contextual embeddings that overcomes the typical limitations of n-gram-based metrics (e.g. synonyms, paraphrases), allowing translations that are different from the references, yet clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…MASS allows the decoder to predict successive sequence fragments to improve the decoder's language modelling capabilities. On the other hand, finetune the strong NMT baseline with BertScore can amend overfitting and effectively overcome the typical limitations of n-gram matching [9], they use BertScore as the objective function for fine-tuning. Wei et al [10] leverage a pre-trained Transformer encoder based on contrastive learning to enrich the representations of bilingual.…”
Section: Related Workmentioning
confidence: 99%
“…MASS allows the decoder to predict successive sequence fragments to improve the decoder's language modelling capabilities. On the other hand, finetune the strong NMT baseline with BertScore can amend overfitting and effectively overcome the typical limitations of n-gram matching [9], they use BertScore as the objective function for fine-tuning. Wei et al [10] leverage a pre-trained Transformer encoder based on contrastive learning to enrich the representations of bilingual.…”
Section: Related Workmentioning
confidence: 99%
“…Various methods have been proposed to tackle this problem (Pan et al, 2023). From training-time correction Li et al, 2019;Jauregi Unanue et al, 2021;Zelikman et al, 2022;Huang et al, 2022) to post output generation refinement (Madaan et al, 2023;Shinn et al, 2023;Zhang et al, 2023;Pan et al, 2023;Yu et al, 2023;Gou et al, 2023;Paul et al, 2023;Akyurek et al, 2023), these methods have shown the impact that iterative self-refinement and proper feedback can have on the performance of LLMs.…”
Section: Introductionmentioning
confidence: 99%